Ethnic diversity, democracy, and health: Theory and evidence. Issue 3 (September 2015) - Kotera, Go; Mizuno, Nobuhiro; Okada, Keisuke; Samreth, Sovannroeun
Abstract This paper examines the relationship among ethnic composition, political regimes, and social welfare. We provide a simple model which divides individuals in each ethnic group into two types of individuals: the benevolent and the self-interested. Each individual determines whether or not to run for office. A policy maker, who allocates government budget among ethnic groups, is chosen among the candidates by voting. In a democracy, all individuals can run for office and can vote in the election. In a dictatorship, the right to run for election and the right to vote are limited to a specific ethnic group. We investigate how ethnic diversity affects selection of a politician and the resulting policy choices in democratic and dictatorial regimes. Ethnic composition affects electoral outcome and policy payoff. Thus, individuals׳ incentive to run for election depends on ethnic composition. The size of ethnic group in power also affects social welfare. Our model derives (1) a negative relationship between ethnic diversity and social welfare, both in a democracy with a dominant group and in a dictatorship, and (2) a non-monotonic relationship in a democracy without a dominant group. In the empirical examination, employing health outcomes as the proxy for the social welfare, our theoretical results are supported by evidence from the data of 157 countries.